Can Verbal Interview Decrease Preoperative Anxiety and Postoperative Discomfort in Oral and Maxillofacial Surgery Patients?: A Randomized Clinical Trial - Kocaturk, Selin; Gur, Zeynep Busra; Gursoytrak, Burcu (Journal of oral and maxillofacial surgery, 2024)
Preoperative anxiety is a condition that can be seen frequently in oral and maxillofacial surgery patients and affects the recovery process. The aim of this study was to determine the effect of preoperative educational or informative interviews on preoperative anxiety levels and postoperative discomfort in patients undergoing oral and maxillofacial surgery. This prospective randomized clinical trial involved patients who underwent oral and maxillofacial surgery at Aydın-Adnan-Menderes University, Oral and Maxillofacial Surgery Hospital. Patients with neurological or psychological disorders, a history of previous psychiatric drug use, those who used anxiolytic or sedative drugs before surgery, those who required postoperative anxiolytic and opioid administration, or patients who underwent nonstandard surgical and anesthesia protocols were excluded. Preoperative educational or informative interview is the exposure variable. Subjects were randomly assigned to the intervention and control groups. The primary outcome variable was preoperative anxiety measured by the Spielberger State-Trait Anxiety Inventory and the Amsterdam Preoperative Anxiety and Information scale (APAIS). The secondary outcome variables were postoperative pain measured by visual analog scale at the first and sixth hours, postoperative nausea (repeated gagging or spitting), and postoperative vomiting (active vomiting) were observed within 6 hours following general anaesthesia. The study's covariates were age, weight, sex, American Society of Anesthesiologists Physical Status Classification System score, marital status, edicational background, surgery procedure, anesthesia procedure, duration of surgery, and recovery time. The χ2 and student t-tests were used to compare primary predictor and covariates against outcome variables. A P value <.05 was considered significant. A total of 92 patients were included in this study, with 46 randomized to intervention group and 46 to control group. The mean age (37.78 ± 13.94 years vs 33.34 ± 15.17 years, P = .16) and sex differences (female/male: 16/30(34.8/65.2) versus 26/20(56.5/43.5), P = .06) were comparable between groups. While higher values were recorded in the average anxiety scores in the control group than in the study group, statistically significant differences were found [Spielberger State-Trait Anxiety Inventory-S (37.36 ± 10.87 vs 52.39 ± 12.13) (P < .01), APAIS-T (15.82 ± 5.35 vs 21.39 ± 6.69) (P < .01), APAIS-A (4.17 ± 2.12 vs 6.47 ± 2.15) (P < .01), APAIS-B (5.76 ± 2.03 vs 7.65 ± 2.60) (P < .01), and APAIS-C (6.04 ± 2.47 vs 7.21 ± 2.38), (P < .05)]. At the same time, there was also a significant difference in terms of early postoperative pain [(2.08 ± 2.77 vs 3.43 ± 2.86), (P = .02)] and postoperative nausea [12/34 (26.1/73.9) versus 25/21(54.3/45.7), (P = .01)]. Oral and maxillofacial surgery causes significant situational anxiety. This study showed that preoperative educational or informative interviews reduced preoperative anxiety levels and postoperative discomfort, such as early postoperative pain, nausea, and vomiting.